Challenges Faced in Translating the Benefits of Surfactant Replacement Therapy to a Resource-Limited Setting - Hamilton, N.; Trotman, Helen (American Journal of Perinatology, 2017)
Aim To determine the challenges, if any, in translating the benefits of surfactant replacement therapy (SRT) to a resource-limited setting.Method This was a retrospective descriptive study comparing the outcome of 75 cases who received surfactant and 69 controls who did not at the University Hospital of the West Indies during the period 2001 to 2011. Descriptive analyses were performed. Statistical significance was taken at the level p < 0.05.Results Only 13% of neonates with respiratory distress syndrome received surfactant therapy. The median time of surfactant administration was 16.5 hours (interquartile range: 6–37 hours). The mean ± standard deviation time between repeat doses was 19.1 ± 14 hours. There was no difference in mortality between cases (67%) and controls (59%) (p = 0.32). However, the cases who survived were less mature (28.3 ± 2 weeks) and less clinically stable (CRIB II [Clinical Risk Index for Babies] score: 8.2 ± 3) than their controls who survived (30.0 ± 2 weeks; CRIB II score: 6.0 ± 3) (p = 0.01). There was no difference in mean gestational age or CRIB II scores between nonsurviving cases and controls. A high incidence of sepsis, pneumothoraces, and pulmonary hemorrhage was noted in both cases and controls.Conclusion SRT did not improve the overall outcome in preterm neonates treated with RDS. Challenges encountered in optimizing SRT included affordability and accessibility of surfactant, supportive equipment, and supportive therapies, as well as a high incidence of complications related to prematurity.
Keywords: challenges of SRT in resource-limited settings; outcome of neonates with RDS in a resource-limited setting; SRT in neonates with RDS in resource-limited settings; SRT in low and- middle-income countries